ALTERNATIVES OF FOREIGN TRADE POLICY IN THE DEVELOPING COUNTRIES IN THE CONTEXT OF SEARCHING THE WAYS TO REDUCE POVERTY - Adamyk, Viktoriia (Journal of European Economy, 2018)
The problem of developing countries’ choice of the optimal foreign trade strategy through the prism of poverty reduction is considered. Attention is focused on the arguments in favour of free-trade and protectionism, as well as the positive and negative consequences of implementing the export-oriented growth strategy. The main conceptual approaches to the study of the impact of international trade liberalization on the economic situation of the developing countries are grouped together. Based on the analysis, it has been shown that the concept of ultra-liberalism is unacceptable for the development of Periphery countries in the context of increasing their welfare. The focus is on the implementation of an export-oriented strategy for the development of poor countries, and these groups of Periphery countries are presented, where this strategy can be successful. The main reasons for the low efficiency of export expansion of developing countries are determined, and the directions of its increase are proposed, which concern, first and foremost, the need for the internal institutional transformation of these countries. JEL: F13.